PERTUMBUHAN RUMPUT LAUT KAPPAPHYCUS ALVAREZII HASIL KULTUR JARINGAN - Nunik Cokrowati; Andy Arjuni; Rusman Rusman (Jurnal Biologi Tropis, 2018)
ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ  The purpose of this study is to determine the right planting point and seed weight to produce optimal growth Kappaphycus alvarezii. Seaweed cultivation method used is bottom off method and seed used is tissue culture seaweed. This research was conducted from February to April 2016 at Nambung beach, Sekotong Subdistrict, West Lombok regency, West Nusa Tenggara Province. This research used experimental method in field with experimental design that used is Factorial Random Design (Factorial RAL). Treatment consists of 2 factors, where the first factor is 3 different planting point (10 meters from coastline, 20 meter from coastline and 30 meters from the coastline) and the second factor is the weight of different seeds (1.5 gram and 50 gram seed weight). The results showed that the planting position of seaweed and the weight of the seeds used gave effect to absolute growth. The interaction between planting position and seed weight also gives Kappaphycus alvarezii a significantly different growth. The conclusion of this research is the use of planting point and seed weight give interaction to each other.Keywords: growth, tissue culture, bottom off method, weight, cultivated